2014
DOI: 10.1177/0021998314528735
|View full text |Cite
|
Sign up to set email alerts
|

In situ characterization of direction-dependent cure-induced shrinkage in thermoset composite laminates with fiber-optic sensors embedded in through-thickness and in-plane directions

Abstract: This study develops a fiber-optic-based technique for in situ characterization of direction-dependent cure-induced shrinkage in thermoset fiber-reinforced composites. A procedure is established to embed fiber Bragg grating (FBG) sensors in composite out-of-plane directions and to measure key through-thickness chemical cure shrinkage directly under practical curing conditions. First, sensitivity of the proposed method is evaluated through comparison with a standard technique (i.e. thermo-mechanical analysis (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 46 publications
5
18
0
3
Order By: Relevance
“…The observed sudden change in slope is a result of the cure shrinkage, which occurs when the material transforms from a liquid to a rubbery state. The resin gels, as confirmed through different investigations in the literature using in-situ strain measurements during processing [26][27][28]. This allows the determination of the point of gelation at a temperature of 163.5 °C, which is consistent with other investigations on the 8552-epoxy system with a heating rate in the test of around 2.5 K/min [26,29].…”
Section: Fig6: Temperature Curve Of the Modified Curing Cyclesupporting
confidence: 85%
“…The observed sudden change in slope is a result of the cure shrinkage, which occurs when the material transforms from a liquid to a rubbery state. The resin gels, as confirmed through different investigations in the literature using in-situ strain measurements during processing [26][27][28]. This allows the determination of the point of gelation at a temperature of 163.5 °C, which is consistent with other investigations on the 8552-epoxy system with a heating rate in the test of around 2.5 K/min [26,29].…”
Section: Fig6: Temperature Curve Of the Modified Curing Cyclesupporting
confidence: 85%
“…[14][15][16][17] However, it is important to note that the amount of strain change measured by FBG does not always coincide with the value of processinduced strain in the laminate. In our previous paper, 19 it was confirmed that chemical-cure shrinkage strain of thermosetting composites measured by FBG sensors changes depending on the distance from the edge of the optical fiber to the point of FBG and the elastic modulus of the matrix resin E m . This phenomenon is attributed to shear lag at the edge of the optical fiber.…”
Section: Influence Of Shear Lag On Fbg Strain Measurementmentioning
confidence: 61%
“…Следова-тельно, для получения достоверных значений деформации усадки следует использовать ВБР с малой физической длиной (1-2 мм). Расхождение в измеренных значениях усадки связующего для ВБР, размещенных в плоскости слоя и перпендикулярно слоям при одинаковых итоговых смещениях, объясняется тем, что по мере протекания реакции отверждения модуль упругости связующего возрастает, а эффективная длина передачи усилия уменьшается [9,12] Остывание образца, зафиксированное на 5-м участке, вносит наибольший вклад в абсолютную величину накопленных остаточных технологических деформаций, так как в стекловидном состоянии время релаксации накопленных остаточных напряжений значительно вырастает в сравнении с вязкоупругим состоянием [9]. Величина смещения длин волн ВБР на данном участке определяется величиной ТКЛР полимерной матрицы.…”
Section: влияние удаления вбр от торца оптоволокна на величину измереunclassified
“…Данный метод считается одним из основных для непосредственного измерения остаточных технологических деформаций, в том числе для определения величины усадки связующего. Хотя измерение остаточных технологических деформаций перпендикулярно слоям представляет наибольший интерес ввиду того, что в реальных конструкциях со сложными схемами армирования измерение остаточных деформаций в плоскости малоинформативно, измерение деформаций перпендикулярно слоям с помощью ВБР приведено только в работах [9,10]. В частности, авторы работы [9] представили результаты измерения остаточных технологических деформаций перпендикулярно слоям для однонаправленного углепластика при наличии и в отсутствие технологической оснастки.…”
unclassified
See 1 more Smart Citation